Komunikasi Digital dan Monetisasi Kreatif: Affiliate, Ads, dan Kolaborasi Merek - Wulan Purnama Sari; Claribel Halim; Tracy Zagitania; William Pradipta (Journal of Indonesian Society Empowerment, 2026)
The contemporary media ecosystem rapidly shifts message production to algorithm-based platforms, generating economic value from digital content. However, this opportunity must be balanced with adequate marketing communication literacy among the younger generation, particularly high school students, to navigate emerging ethical and compliance challenges. Addressing this urgency, this Community Service (PKM) program aims to enhance digital marketing communication literacy and responsible monetization skills among students at Santa Maria High School in Cirebon. The intervention is designed as an interactive face-to-face workshop covering two main areas: (1) core concepts including integrated message planning, channel selection, and ethical compliance (sponsor disclosure, copyright, privacy); and (2) structured practice involving scriptwriting, content production, and monetization simulations (affiliate, platform advertising, and brand collaboration), utilizing Claude Sonnet 4.6 for publication ideation and optimization. The theoretical framework integrates Integrated Marketing Communications, Uses and Gratifications, and Diffusion of Innovations to ensure message consistency and readiness to adopt new digital features. Evaluation is conducted through pre-post-test questionnaires to assess improvements in knowledge, attitudes, and practical readiness. Program outputs include formal reports, national journal publications, prototype reports, and intellectual property rights. Ultimately, this initiative aligns with the RIP-PKM agenda to strengthen community communication quality and develop a talent-based creative economy that is ethical, effective, and measurable. Ekosistem media kontemporer bergerak cepat ke ranah digital, menempatkan produksi dan sirkulasi pesan pada platform berbasis algoritma, serta membuat nilai ekonomi tercipta dari konten yang diproduksi. Peluang ini juga harus diimbangi dengan kesiapan literasi komunikasi pemasaran di kalangan generasi muda, khususnya pelajar SMA. Adanya bentuk baru dari pemasaran digital juga menimbulkan kendala baru dalam hal isu etika dan kepatuhan. Di sinilah urgensi program Pengabdian kepada Masyarakat (PKM) untuk sekolah menengah. Program Pengabdian kepada Masyarakat (PKM) ini bertujuan meningkatkan literasi komunikasi pemasaran digital dan kapasitas keterampilan monetisasi yang bertanggung jawab pada siswa SMA Santa Maria Cirebon. Intervensi dirancang dalam bentuk workshop tatap muka, yang berisikan: (1) penguatan konsep inti—perencanaan pesan terpadu, pemilihan kanal, dan kepatuhan etika (disclosure sponsor, hak cipta, privasi); (2) praktik terstruktur—penyusunan naskah, produksi konten, serta simulasi alur monetisasi melalui tiga skema utama (afiliasi, iklan platform, dan kolaborasi merek) termasuk pemanfaatan alat berbasis AI untuk ide dan optimasi publikasi. Kerangka teoretis mengintegrasikan Integrated Marketing Communications guna memastikan konsistensi pesan, relevansi kebutuhan audiens, dan kesiapan adopsi fitur baru. Evaluasi dilakukan melalui pra–pasca uji (kuesioner) untuk menilai peningkatan pengetahuan, sikap, dan kesiapan praktik. Luaran meliputi laporan, publikasi di jurnal nasional, laporan prototype, dan hak kekayaan intelektual berupa hak cipta. Program ini selaras dengan RIP-PKM pada agenda penguatan kualitas komunikasi masyarakat dan kontribusi pada pengembangan ekonomi kreatif berbasis talenta muda yang etis, efektif, dan terukur.